Is It Time Alpha-1 Antitrypsin Deficiency Had a Specific Patient Reported Outcome Measure? A Review - De Soyza J; Chien HY; Onasanya AA; Turner AM (Patient Related Outcome Measures)
Joshua De Soyza, Hung-Yeh Chien, Adeola Ayodotun Onasanya, Alice M Turner Institute of Applied Health Sciences, University of Birmingham, Birmingham, UKCorrespondence: Joshua De Soyza, Email j.desoyza@bham.ac.ukAbstract: Alpha-1 antitrypsin deficiency (AATD) is a rare cause of chronic lung and liver disease without its own patient reported-outcome measure (PROM). PROMs for Chronic Obstructive Pulmonary Disease (COPD) are commonly used instead, but AATD differs from COPD in several ways. We reviewed whether the PROMs used in the AATD literature adequately assess quality-of-life in these patients. 11 studies used PROMs as their primary outcomes; 21 included them as secondary outcomes. The St George’s Respiratory Questionnaire (SGRQ) was the most commonly used PROM, used by 7 of the 11 primary outcome studies. Others included the COPD Assessment Tool, SF-36, LCOPD, EQ-5D, and the Chronic Respiratory Diseases Questionnaire. Several studies assessed SGRQ as being associated with respiratory disease severity as measured by FEV1% predicted, exacerbation rate, oxygen use and exercise tolerance. However, no studies used PROMs which included assessment of liver-related symptoms, other extra-pulmonary manifestations of AATD, or concerns related to genetics or finances. These factors are likely to have an impact on quality of life in AATD. A specific AATD-PROM is therefore required to holistically address the quality of life effects of an AATD diagnosis.Keywords: alpha-1 antitrypsin deficiency, COPD, chronic liver disease, rare diseases